2001
DOI: 10.1007/bf02772157
|View full text |Cite
|
Sign up to set email alerts
|

Serial extraction of endosperm drillings (SEED)—A method for detecting transgenes and proteins in single viable maize kernels

Abstract: We have developed a method for detecting a transgene and its protein product in maize endosperm that allows the kernel to be germinated after analysis. This technique could be highly useful for several monocots and dicots. Our method involves first sampling the endosperm with a hand-held rotary grinder so that the embryo is preserved and capable of germination. This tissue is then serially extracted, first with SDS-PAGE sample buffer to extract proteins, then with an aqueous buffer to extract DNA. The product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Endosperm material from individual kernels was collected using a hand-held rotary grinder (Dremel) as described (Sangtong et al 2001). Extracted proteins were separated by electrophoresis on a 12% SDS-PAGE (Acrylamide/bis 37.5:1) gel (Laemmli 1970) in the presence of β-mercaptoethanol using a Mini-Protean II Electrophoresis Cell from BIO-RAD with a 20-well comb.…”
Section: Sds-pagementioning
confidence: 99%
See 1 more Smart Citation
“…Endosperm material from individual kernels was collected using a hand-held rotary grinder (Dremel) as described (Sangtong et al 2001). Extracted proteins were separated by electrophoresis on a 12% SDS-PAGE (Acrylamide/bis 37.5:1) gel (Laemmli 1970) in the presence of β-mercaptoethanol using a Mini-Protean II Electrophoresis Cell from BIO-RAD with a 20-well comb.…”
Section: Sds-pagementioning
confidence: 99%
“…Polymerase chain reaction DNA was extracted and purified from the endosperm pellet remaining in the 96-well plate after extraction of the proteins with SDS-PAGE (Sangtong et al 2001). Leaf DNA was prepared using the Puregene DNA isolation kit (Gentra Systems, Minneapolis, Minn.).…”
Section: Immuno-blot Analysismentioning
confidence: 99%
“…Abnormalities in foreign gene transmission have been reported. In two extreme cases, Hood et al (1997) observed that transgenic plants expressing avidin were male sterile as a result of the effect of the transgene, while Sangtong et al (2001) observed that transgenic maize plants expressing the wheat glutenin 1DX5 gene did not transmit the gene through the pollen.…”
Section: Stability Of Gene Expression and Transmission Of The Transgenementioning
confidence: 99%
“…To identify kernels expressing LT-B for planting for the next generation, individual kernels from each ear (two ears per event) were analyzed by a partial destruction method (Sangtong et al, 2001). With the use of a fine drill and without damaging the embryo, part of the endosperm from each kernel was removed for ELIS A analysis.…”
Section: Evaluation Of Protein Productionmentioning
confidence: 99%
See 1 more Smart Citation